Prácticas alimentarias relacionadas con la nutrición infantil en niños menores de cinco años. - Pilco Jiménez, Daniela Estefania; Vera Cordero, Alisson Joely (My University, 2024)
Child malnutrition remains a public health challenge that affects the physical, cognitive, and motor development of children under five years old. This study determined the relationship between caregivers’ feeding practices and the nutritional status of children enrolled in an Ecuadorian educational institution. Using a quantitative, descriptive, and cross-sectional design, 185 children were evaluated through a validated questionnaire on nutritional practices. Results showed that most children have anthropometric parameters within normal ranges, although cases of malnutrition and overweight persist. Predominantly healthy habits were identified, such as regular consumption of fruits, vegetables, and proteins, proper hygiene in food preparation, and frequent complete meals. However, weaknesses were found, including the replacement of healthy snacks with processed ones, consumption of ultra-processed foods, and low participation in nutrition training. Caregivers’ education and socioeconomic status directly influence these practices: a medium education level and unemployment negatively affect food security. It is concluded that strengthening nutritional education, ensuring access to healthy foods, and reinforcing public policies are necessary. Nursing staff play a key role in improving family nutritional literacy and promoting healthy food environments that support comprehensive child growth from early childhood..
La desnutrición infantil sigue siendo un desafío de salud pública que afecta el desarrollo físico, cognitivo y motor de niños menores de cinco años. Esta investigación determinó la relación entre las prácticas alimentarias de los cuidadores y el estado nutricional infantil en estudiantes de una unidad educativa ecuatoriana. Con un diseño cuantitativo, descriptivo y transversal, se evaluó a 185 niños mediante un cuestionario validado sobre prácticas nutricionales. Los resultados mostraron que la mayoría presenta parámetros antropométricos adecuados, aunque persisten casos de desnutrición y sobrepeso. Se identificó un predominio de hábitos saludables como consumo de frutas, verduras y proteínas, adecuada higiene en la preparación de alimentos y frecuencia de comidas completas. Sin embargo, persisten debilidades como la sustitución de snacks procesados, consumo de ultraprocesados y escasa participación en capacitaciones sobre nutrición. La educación de los cuidadores y su situación socioeconómica inciden directamente: el nivel educativo medio y el desempleo afectan la seguridad alimentaria. Se concluye que es necesario fortalecer la educación nutricional, garantizar acceso a alimentos saludables y reforzar políticas públicas. El personal de enfermería desempeña un rol clave para promover entornos alimentarios saludables desde la primera infancia.
Keywords: HABITOS ALIMENTARIOS; ESTADO NUTRICIONAL; NIÑOS; ALIMENTACION COMPLEMENTARIA